Differentiated Learning in Teaching English Subject of The Merdeka Curriculum - Erwin Oktoma; Muhammad Aprianto Budie Nugroho; Yayan Suryana; Mujtaba Jamal (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2025)
Objective: This study examines the implementation of differentiated learning in teaching English at the senior high school level, focusing on its strengths and challenges within the Merdeka Curriculum framework. Differentiated learning is applied through content, process, and product, allowing teachers to tailor instruction to students’ needs. The findings highlight benefits such as enhancing student engagement, accommodating diverse learning styles, and fostering personalized instruction. However, challenges include complex lesson planning, inadequate school facilities, and inconsistencies in teaching approaches. The study emphasizes the need for teacher training, technical support, and infrastructure improvements to optimize its implementation. Method: This research employs a descriptive qualitative approach at Senior High School 1 Garawangi, Kuningan Regency, West Java. Data were collected through classroom observations and teacher interviews with 13 structured questions. The analysis explores how differentiated learning aligns with the Merdeka Curriculum, along with its practical challenges. Results: The study reveals that differentiated learning enhances student participation and learning outcomes but presents difficulties such as complex preparation, resource constraints, and varied teacher competencies. The study suggests enhancing teacher training, providing technical guidance, and improving school facilities. Novelty: This research provides new insights into differentiated learning within the Merdeka Curriculum, specifically in English language teaching, contributing to effective instructional strategies in Indonesia.